A PERFORMANCE GUIDE OF LIGHT LYRIC COLORATURA SOPRANO REPERTOIRE IN FOUR EARLY OPERAS BY JEAN-PHILIPPE RAMEAU (1733-1745) - (:unkn) unknown (My University, 2012)
A PERFORMANCE GUIDE OF LIGHT LYRIC COLORATURA

SOPRANO REPERTOIRE IN FOUR EARLY OPERAS

BY JEAN-PHILIPPE RAMEAU (1733-1745)

BY: CÉLIA ZAMBON WOLLENBERG

This study investigates French eighteenth&ndashcentury musical aesthetics as they relate to style and performance practice in the early operas of Jean-Philippe Rameau. Through the analyses of five pieces for light lyric coloratura soprano, selected from four different operas, this document guides performers and teachers toward appropriate and historically informed performances. The study is divided into five sections. The first chapter establishes the need for the study, its organization, and related literature. The second chapter provides a background describing the performance history and the plot line for each of the four operas. The third chapter offers general considerations regarding eighteenth&ndashcentury musical ornamentation and the etiquette of gesture: after a brief exposé on French baroque aesthetics regarding opera performance in the early eighteenth century, this chapter provides a thorough listing of melodic and rhythmic ornamentation, as well as considerations regarding the pronunciation of text; the chapter concludes with a few considerations concerning gesture on the eighteenth-century stage. The fourth chapter provides the analyses of five selected pieces. Each piece is placed within its dramatic context, and each text is translated in IPA (International Phonetic Alphabet) and in English. In addition, a thorough musical analysis is conducted for each piece, including considerations of: form and harmony; texture and instrumentation; melodic contour; meter, rhythm, tempo and dynamics; diction, ornamentation and rhythmic alteration; and performance gesture and skill level.
Keywords: Operas--Analysis, appreciation; Music--18th century; Vocal music--History and criticism; Embellishment (Music)--18th century